2017
DOI: 10.4103/jomfp.jomfp_217_16
|View full text |Cite
|
Sign up to set email alerts
|

Keratoacanthoma of the lip: A case report with emphasis on histogenesis

Abstract: Keratoacanthoma (KA) is a benign epithelial tumor which presents clinically as a proliferating dome-shaped keratin-filled crater. The lesion occurs predominantly upon sun-exposed areas of the body and is known to arise from hair follicle. Actinic rays are a major contributing factor in the etiology. It simulates grossly as well as microscopically a low-grade squamous cell carcinoma. KAs occur habitually on the mucous membrane as well, but their origin in these cases is debatable, owing to the lack of hair foll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…Ramos et al [ 7 ] suggested that the KA growth cycle is similar to the life cycle of hair follicles, hinting at the possibility that KA may be derived from hair follicle cells. Kamath et al [ 3 ] found that KA cells can differentiate into cells similar to those of the outer root sheath of hair follicles, further supporting the possibility that skin KA originates from hair follicles. Since the lip mucosa lacks the hair follicle structure of the skin, lip KA may be derived from other structures of the lip mucosa.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Ramos et al [ 7 ] suggested that the KA growth cycle is similar to the life cycle of hair follicles, hinting at the possibility that KA may be derived from hair follicle cells. Kamath et al [ 3 ] found that KA cells can differentiate into cells similar to those of the outer root sheath of hair follicles, further supporting the possibility that skin KA originates from hair follicles. Since the lip mucosa lacks the hair follicle structure of the skin, lip KA may be derived from other structures of the lip mucosa.…”
Section: Discussionmentioning
confidence: 97%
“…The cause of KA remains unknown. Sunlight exposure and UV radiation accumulation are considered to be the main risk factors for KA[ 3 ]. Related causes include viral infections, especially human papillomavirus[ 2 ], reduced immune function[ 4 ], trauma[ 5 ], and genetic factors[ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…Keratoacanthoma is a self-limiting benign proliferative epithelial lesion that usually presents an initial proliferative phase, followed by a maturation phase and a involutive or stationary phase, that may or may not have spontaneous regression. In contrast, the squamous cell carcinoma, in any localization, is a malignant epithelial neoplasia that does not undergo spontaneous involution [5,9].…”
Section: Discussionmentioning
confidence: 99%
“…They may appear clinically like squamous cell carcinomas, and differentiation arises from histological analysis. The most common treatment modality is complete excision as this allows for histological examination of the lesion in its entirety [33].…”
Section: Keratoacanthomamentioning
confidence: 99%